Reduction of ER stress via a chemical chaperone prevents disease phenotypes in a mouse model of primary open angle glaucoma - Gulab Zode; Markus H. Kuehn; Darryl Nishimura; Charles Searby; Kabhilan Mohan; Siniša D. Grozdanić; Kevin Bugge; Michael G. Anderson; Abbot F. Clark; Edwin M. Stone; Val C. Sheffield (2011)
Mutations in myocilin (MYOC) are the most common genetic cause of primary open angle glaucoma (POAG), but the mechanisms underlying MYOC-associated glaucoma are not fully understood. Here, we report the development of a transgenic mouse model of POAG caused by the Y437H MYOC mutation; the mice are referred to herein as Tg-MYOCY437H mice. Analysis of adult Tg-MYOCY437H mice, which we showed express human MYOC containing the Y437H mutation within relevant eye tissues, revealed that they display glaucoma phenotypes (i.e., elevated intraocular pressure [IOP], retinal ganglion cell death, and axonal degeneration) closely resembling those seen in patients with POAG caused by the Y437H MYOC mutation. Mutant myocilin was not secreted into the aqueous humor but accumulated in the ER of the trabecular meshwork (TM), thereby inducing ER stress in the TM of Tg-MYOCY437H mice. Furthermore, chronic and persistent ER stress was found to be associated with TM cell death and elevation of IOP in Tg-MYOCY437H mice. Reduction of ER stress with a chemical chaperone, phenylbutyric acid (PBA), prevented glaucoma phenotypes in Tg-MYOCY437H mice by promoting the secretion of mutant myocilin in the aqueous humor and by decreasing intracellular accumulation of myocilin in the ER, thus preventing TM cell death. These results demonstrate that ER stress is linked to the pathogenesis of POAG and may be a target for treatment in human patients.